(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: To present the key ﬁndings and global insights from the Third set of Global Observatory for Physical Activity (GoPA!) Country Cards. Methods: Data on demographics, surveillance, policy, and research indicators were collected for 218 countries to create country-speciﬁc physical activity (PA) proﬁles. Using a standardised methodology, the GoPA! Working Group organised the indicators and launched a new online workﬂow system for review and approval that will be completed by December 2024. Potential contacts were identiﬁed in each country through databases and expert recommendations, invited to verify the Country Cards for accuracy, and encouraged to translate the cards into their native language. Indicators included country, capital, population, urban population, life expectancy, Gini Index, Human Development Index, non-communicable diseases (NCDs) mortality, overall PA prevalence estimates, policies, guidelines, surveillance, research, and country capacity for PA promotion. New measures, such as premature NCD mortality risk, Human Capital Index, Democracy Index, and PA estimates by domain (active leisure, transport), were introduced. New representations were added, including equiplots for gender inequalities in adult PA prevalence and research. The capacity pyramid for PA promotion was updated to reﬂect policy availability and implementation, as well as surveillance data and periodicity. Results: Preliminary results show that for 163 countries (74.8%), Country Contacts conﬁrmed the accuracy of information. These contacts were from academia (65.6%), government (20.7%), non-proﬁt organisations (6.2%), national agencies (3.9%), or other (3.6%). PA surveillance, policy, and research data were available for 96.3%, 94.5%, and 90.8% of these countries, respectively. Gender equiplots highlighted signiﬁcant inequalities in adult PA prevalence estimates and research outputs (ﬁrst and senior authors), especially in low- and middle-income countries. The updated PA promotion capacity pyramid showed that while 70 countries reported standalone PA policies, only 33 demonstrated high implementation levels. All 218 Country Cards are available in English, with select cards translated into an additional 30 languages. Conclusions: The new indicators and ﬁndings from the Third edition of the GoPA! Country Cards offer a more comprehensive picture of the global PA landscape and emphasise the importance of effective PA surveillance, policy, and research. Support/Funding Source: Global Observatory for Physical Activity (GoPA!).